Effectivity of Percutaneous Nephrolithotomy versus Retrograde Intrarenal Surgery on Kidney Stone: A Single-center Experience - Muhammad Fachri Fauzi; Tarmono Djojodimedjo; Mohammad Ayodhia Soebadi; Mohamad Fairuz Mohamad Sharin (Biomolecular and Health Science Journal)
Introduction: Urinary tract stones are one of the most prevalent urological diseases worldwide. Percutaneous nephrolithotomy (PCNL) and retrograde intrarenal surgery (RIRS) are two primary treatment modalities for the said disease. This study analyzes and compares the clinical characteristics and outcomes of kidney stone patients undergoing PCNL and RIRS in Indonesia. Methods: We retrospectively analyzed patients with urinary tract stones who underwent PCNL and RIRS in a single hospital. Patient characteristics were retrieved from medical records between January 2022 and December 2023. We compared the age, gender, number, size of stones, as well as preoperative imaging, comorbid diseases, and stone-free rate (SFR) of the patients. Results: From January 2022 to December 2023, 116 cases of kidney stones were found in Universitas Airlangga Hospital. Sixteen patients underwent the RIRS procedure, and 100 patients underwent the PCNL procedure. Conclusions: Patients who underwent PCNL procedures for kidney stones are generally men over 40 years old with kidney stones larger than 2 cm and < 2 cm for RIRS procedures. The PCNL procedure has an overall higher SFR than the RIRS procedure, especially for large and complex stones. However, RIRS has a higher success rate for stones under 2 cm. The SFR of both modalities decreases as the Guy’s stone score increases.